Diagnosis, treatment, and functional outcomes for two adolescent female patients with lupus myelitis: a case report - Claus, Deanna; McCoy, Andrew; Ratnasingam, Denesh; Saez, Cristina; Tarshish, Gabriel; Sarmiento, Cristina (Frontiers in Rehabilitation Sciences, 2025)
IntroductionTransverse myelitis is a rare neurologic complication associated with systemic lupus erythematosus (SLE), also known as lupus myelitis. Little is known about the optimal treatment regimen for the disease or the functional outcomes after diagnosis, especially for pediatric patients.MethodsA retrospective case series at a large, academic pediatric tertiary care center was performed to describe the clinical presentation, diagnostic approach, early treatment, and functional outcomes in two pediatric patients diagnosed with lupus myelitis as a presenting sign of new-onset SLE.ResultsDescription of baseline patient characteristics, presenting symptoms and clinical features, laboratory work-up and neuroimaging findings, immunomodulatory therapy, complications, and rehabilitation functional outcomes are described for two adolescent patients diagnosed with lupus myelitis. Both patients presented with features that were initially mistaken for other neurologic conditions. The combination of longitudinally extensive lesions of the spinal cord on neuroimaging and laboratory findings suggestive of an autoimmune process ultimately led to the diagnoses of lupus myelitis and new-onset SLE. Both patients received intravenous and oral corticosteroids, plasmapheresis, rituximab, cyclophosphamide, intravenous immunoglobulin, and acute intensive rehabilitation including physical therapy, occupational therapy, and speech therapy. Both patients demonstrated marked functional improvement in domains of self-care and mobility in the setting of acute inpatient rehabilitation.DiscussionWhile this diagnosis has been described in adult literature, there is limited evidence regarding management or functional outcomes for pediatric cases of lupus myelitis. Collaboration between rheumatology and rehabilitation teams allowed for a coordinated approach to achieve medical and functional goals. Early diagnosis, treatment, and acute inpatient rehabilitation led to significant improvement in functional outcomes for the two pediatric patients in this study.